Doublecortin (DCX) immunoreactivity in hippocampus of chronic refractory temporal lobe epilepsy patients with hippocampal sclerosis - D`Alessio, Luciana (2010)
Introduction: Status epilepticus increases the production of new neurons (hippocampal neurogenesis) and promotes aberrant migration. However chronic experimental models of epilepsy and studies performed in human epilepsy showed controversial results suggesting a reduction in hippocampal neurogenesis in late stages of the disease. Doublecortin (DCX) has been validated to determine alterations in the production of new neurons in the human hippocampus. Objectives: Determine DCX expression in human hippocampal sclerosis (HS) from patients who underwent epilepsy surgery for refractory temporal lobe epilepsy (TLE). Methods: Hippocampal sections of 9 patients with HS and TLE who underwent surgery, were processed using immunoperoxidase for DCX. Archival material from 5 normal post-mortem hippocampus were simultaneously processed. Results: Significantly lower staining intensity was observed in DCX-positive neurons localized in dentate gyrus (DG) and in CA1 of epileptic hippocampus; lower DCX reactive area was observed in pyramidal layers of CA1; and a reduced in the mean number of DCX-positive neurons were determined in DG compared to normal hippocampus (p < 0.05). Conclusions: This study found a decrease in DCX expression in hippocampus of patients with HS and chronic and refractory TLE suggesting alterations in NG and hippocampal synaptogenesis with potential cognitive and emotional repercussion.